Inter-Modelling with Graphical Constraints: Foundations and Applications - de Lara, Juan; Guerra, Esther (Electronic Communications of the EASST, 2012)
Model-Driven Engineering (MDE) promotes an active use of models in the different phases of the development, so that the construction of systems usually involves a number of models expressed in different languages and levels of abstraction; therefore, there is the constant need to compare, generate and update models and their relations. We call inter-modelling to the activity of building models that describe how modelling languages should be related. This includes many MDE activities like the specification of model-to-model transformations, the definition of model matching and traceability constraints, and the development of inter-model consistency mantainers. While most approaches build different operational programs to handle each activity separately, we propose using a high-level specification language called PaMoMo to specify inter-models in a declarative, graphical, bidirectional way. This specification can be compiled into operational mechanisms to solve different inter-modelling activities like transformation, model comparison and traceability support. Other usage scenarios for PaMoMo are the specification of transformation contracts and the automated testing of transformations.